From consumer to prosumer: a supply chain revolution in 3D printing. Issue 2 (4th March 2019) - Halassi, Sam; Semeijn, Janjaap; Kiratli, Nadine
Abstract : Purpose: Recent technological advances in three-dimensional printing (3DP) may disrupt traditional manufacturing and logistics processes. Because the increasing availability of 3DP service centers, affordable 3D printers, and online platforms empower consumers to design and print objects at home, companies must determine the motives that lead consumers to become prosumers so that they can establish appropriate business models and supply chains. Accordingly, the purpose of this paper is to identify factors that drive consumer acceptance and use of 3DP technologies. Design/methodology/approach: The explanatory conceptual framework, based on the extended unified theory of acceptance and use of technology, undergoes empirical testing with a sample of 196 3DP consumers who participated in an online survey. Findings: Facilitating conditions, hedonic motivation and a do-it-yourself mentality are key determinants of consumer acceptance and use intention of 3DP technology. Practical implications: Companies can use these insights about consumers' motivation to determine whether their use of 3DP technology threatens current business models or supply chains. In turn, they can develop new ideas about how to adapt these features, as well as identify opportunities for new revenue streams. Originality/value: Unlike most extant literature on 3DP in manufacturing and logistics domains, this study takes consumers' point of view to shed light on an issue typically investigated from an operations management perspective.